Penyanderaan (Gijzeling) Sebagai Upaya Penagihan Pajak Dengan Surat Paksa Menurut Peraturan Perundang-undangan - Budi Budaya; Hotma P. Sibuea; Noviriska (Jurnal Hukum Sasana, 2023)
This research discusses the delegation of authority to grant hostage-taking permission (gijzeling) from the Minister of Finance of the Republic of Indonesia to the Director General of Taxes as seen from the Law of the Republic of Indonesia Number 30 of 2014 on State Administration. This study aims to determine whether granting a hostage-taking permit (gijzeling) can be delegated from the Minister of Finance to the Director General of Taxes. The research method used is the juridical-normative method, namely research that emphasizes the science of law and conducts an inventory of positive law relating to implementing laws and regulations. From this research, it was found that the granting of hostage warrant permits from the Minister of Finance of the Republic of Indonesia can be delegated to the Director General of Taxes. The method of delegation of authority is by the delegation of authority.